Mobile-Assisted Language Learning (MALL) for Academic Writing: A Thematic Analysis of Students’ Attitudes - Sahib, Nurfaizah; Rosmawati Abdul Maing; Dahlia D, Moelier (Universitas Cokroaminoto Palopo, 2026)
This study explores students’ attitudes toward the use of Mobile-Assisted Language Learning (MALL) applications in academic writing classes in the third semester of the English department at Universitas Bosowa. It was limited to the use of WhatsApp, Kahoot, and ChatGPT. Specifically, it investigates how the application supported students’ learning experiences within a constructivist framework. This study employed a qualitative research design involving 15 Participants. The data were collected through interviews and reflective journals. The data were analyzed using a thematic analysis approach. Findings reveal that students demonstrated positive attitudes toward MALL, particularly in terms of enhanced engagement, motivation, and collaborative learning. WhatsApp facilitated peer interaction and idea exchange, Kahoot increased classroom participation through gamification, and ChatGPT provided initial ideas, topics, and writing angles to overcome writer’s block. Overall, the results indicated that integrating mobile applications fosters active participation and autonomy in academic writing, while also requiring careful guidance to balance benefits and challenges. This study suggests that lecturers should strategically integrate MALL tools to enhance academic writing, and further research should examine long-term impacts on writing development across diverse contexts